PROGRAM PANGGUNG CERIA: PENGENALAN DRAMA SEDERHANA UNTUK MENUMBUHKAN KARAKTER DAN IMAJINASI ANAK USIA DINI - Khaerunnisa Khaerunnisa; Mutiarani Mutiarani; Puan Dinaphia Yunan; Rina Nuryani; Tiara Savitri; Anzily Rahma Alia (Universitas Mataram, 2026)
The Panggung Ceria Program: An Introduction to Simple Drama to Cultivate Character and Imagination in Early Childhood is motivated by the importance of providing creative, fun learning media that are in accordance with the developmental characteristics of early childhood. At this stage of development, children have a high curiosity and imagination, so they need stimulation through visual experiences, stories, and meaningful interactive activities. However, learning in some early childhood education institutions is still dominated by basic academic activities so that the space for developing imagination, empathy, and understanding of character values ​​is not optimal. This community service activity aims to introduce simple drama as an educational medium to foster children's imagination and strengthen character values ​​through the stories and characters presented. The implementation method is carried out through a participatory approach with the stages of needs observation, preparation of materials and drama staging, implementation of simple drama performances, and interactive activities in the form of light discussions and reflections with children. The drama presented raises the theme of honesty, courtesy, caring, and compassion with language and storylines that are easily understood by early childhood. The results of the activity show that children show high enthusiasm while watching the performance, are able to understand the moral messages conveyed, and demonstrate the development of imagination through responses, questions, and retellings that they tell after the activity. This program also provides a fun and meaningful learning experience in supporting the strengthening of early childhood character education.